Water quality. Detection and enumeration of Escherichia Coli and coliform bacteria in surface and waste water. Miniaturized method (most probable number) for the detection and enumeration of 7IE. coli7R in surface and waste water Part 3, (15th July 2001) - British Standards Institution,
No abstract available